Development Of Interactive Powerpoint Media About Careing Around Animals In Elementary School Students - Imas Damayanti Lovita; Chusna Arifah; Tesa Esti Rahayu; Iip Hidayat; Karlimah K; Erwin Rahayu Saputra (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study is one of the important components in the process of teaching and learning activities. In the current new normal era, teachers are required to make changes from conventional learning to digital learning. However, the reality on the ground shows that teachers are not prepared to learn media according to the needs of students. The learning media used by the teacher is still in the form of images and text only. Therefore, there is a need for innovation in making learning media that can meet all the needs of students. This study aims to improve the quality of learning and student participation, and develop interactive PowerPoint media that is suitable for use by elementary school students. The research method used in this research is Research and Development (RD) with the DDD-E development model (Decide, Design, Develop, and Evaluate). Data collection techniques, namely observation, interviews, and questionnaires. The data analysis technique used descriptive qualitative analysis. This research was conducted in four elementary schools. The subjects of this study amounted to 84 students of class II on the sub-theme of Caring for Animals Around Me. The research data shows that the percentage of the feasibility level of interactive PowerPoint media according to subject matter experts is 100%, according to learning design experts is 92%, and according to user trial results is 96% with very good qualifications, and according to learning media experts, it is 85% with good qualifications. Based on the results of this study, it can be said that interactive PowerPoint media is appropriate to be used in the learning process for grade II elementary school students.